Dengvaxia®: Prayers Answered or NOT? - Gupta, Deepak (Indian Journal of Community Health, 2016)
Dengvaxia is the first vaccine against dengue that has been developed after decades of toiling to tame the four-strain dengue virus. The questions have already been raised regarding its non-utility for the younger ones and the seronegative population due to ethical concern of non-maleficence (do-no-harm). It is not clear where this leaves the endemic populations suffering for decades from un-resolving morbidity and mortality burdens of dengue fever, and whether this worsens the dilemma of those populations’ rattled-governments planning to ride the approaching bandwagons of mass vaccination programs against dengue. Irrespective, people and personnel living in dengue-endemic regions should welcome hands down this human endeavour to develop Dengvaxia, the first vaccine against dengue.